The development and implementation of a coding scheme to analyse interview dynamics in the British Household Panel Survey - Emanuela Sala; S.C. Noah Uhrig; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2008)
The study of interviewer-respondent interaction that occurs during an interview can give very useful insights into the cognitive process of answering questions, the social dynamics that develop in an interview context and the way these dynamics ultimately impact data quality. Behaviour coding is a technique used to code such interactions. Despite its long-standing use, little is written about the procedures to be followed while developing a coding scheme. This paper provides a practical background on the development and implementation of the behaviour coding scheme adopted to explore interview dynamics in the framework of dependent interviewing. This schema was used to code approximately 150 previously transcribed interviews of the British Household Panel Study Wave 16 pilot. Coding strategies and procedures, coder recruitment and training reliability assessments as well as timetable and costs are documented and discussed.
Keywords: 330